Poly (methyl methacrylate)-graphene oxide supported palladium catalyst: A ligand free protocol for Suzuki and Heck coupling reaction in water medium. Issue 19 (2nd October 2018) - Basak, Puja; Ghosh, Pranab
Abstract: A green and efficient approach for the ligand free Suzuki–Miyaura and Mizoroki–Heck C–C cross coupling reaction using low palladium loaded Graphene oxide-polymer composite catalyst has been described. High yields, easy work-up, easy availability and handling, eco-friendly and reusability of the catalysts are the main aspects of the present method. The simplicity of the entire sequence has made the protocol meritorious as a reasonable contribution to the existing methods in the field of substituted biphenyls and olefins. The supported heterogeneous catalyst was characterized using HRTEM, ICP-AES, PXRD, XPS, TGA, and FT-IR spectroscopy. Graphical Abstract: